Investigation of cation distribution and magnetocrystalline anisotropy of NixCu0.1Zn0.9−xFe2O4 nanoferrites: Role of constant mole percent of Cu2+ dopant in place of Zn2+. Issue 11 (1st August 2017) - Ramakrishna, K.S.; Srinivas, Ch.; Meena, S.S.; Tirupanyam, B.V.; Bhatt, Pramod; Yusuf, S.M.; Prajapat, C.L.; Potukuchi, D.M.; Sastry, D.L.
Abstract: Co-precipitated and 800 °C heat treated Ni-Cu-Zn nanoferrites with chemical formula Ni x Cu0.1 Zn0.9- x Fe2 O4 ( x =0.5, 0.6, 0.7) were prepared because of their potential use as multilayer chip inductors in electromagnetic applications. Their structural, magnetic properties and phase formation were studied using X-ray diffractometer (XRD), field emission scanning electron microscope (FE–SEM), vibrating sample magnetometer (VSM), Mössbauer spectrometer, thermogravimetric analyzer (TGA) and differential scanning calorimeter (DSC). The XRD patterns confirm the cubic spinel structure of the ferrite phase belonging to Fd3m space group. Lattice parameters and cation distributions were obtained by Rietveld refinement of the XRD patterns. The lattice parameter decreases with increase in Ni 2+ ion concentration. Rietveld analysis indicates that Cu 2+ ions predominantly occupy the B -sites and Ni 2+ ions partly going into B -sites but predominantly into A -sites. An excellent agreement is observed between the experimental lattice parameters and lattice parameters theoretically calculated using this cation redistribution. The inversion parameter (λ) observed for Fe 3+ ions by Mössbauer spectroscopy is different from that of Rietveld analysis. Magnetization and Mössbauer spectroscopic measurements indicate that the ferrite nanoparticles are mostly superparamagnetic. The cation redistribution is supposed to alter the magnetocrystalline anisotropy which in turn affects the magnetic parameters of the present ferrite samples. The reduced magnetization is attributed to core-shell interactions and possible canting of A - and B -shell magnetizations. TGA-DSC studies indicate that ferrite formation in the 800 °C heat treated samples is completed but grain growth increases as the particles are subject to the increased temperature. Highlights: Substitution of Cu 2+ hinders the drift of Ni 2+ in the spinel structure. The inversion parameter (λ) for Fe 3+ ions from Mössbauer analysis different from that of Rietveld analysis. Sintering process promotes the change in surface energy near grain boundaries. Cation distribution varies the magnetocrystalline anisotropy of ferrite systems.